1970
DOI: 10.1677/joe.0.0460331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy and Ovarian Hormones on Rna Base Ratios in Specific Rabbit Brain Areas

Abstract: The ribonucleic acid (RNA) base percentages were estimated in the hypothalamus, amygdala, hippocampus, frontal cortex, cerebellum and spinal cord of adult intact female rabbits, and after ovariectomy followed by replacement therapy with oestradiol-17\g=b\,progesterone and oestradiol plus progesterone. The results indicate a lack of effect on the spinal cord, but a variable effect on all other brain regions examined. In response to the various treatments, all regions examined produced RNA very rich in guanosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…(10) have demonstrated that progesterone was able to modify pituitary luteinizing hormone secretion in the rat, even in the absence of circulating oestrogens, through its effects exerted upon the cerebellum and the amygdala. This observation is in line with the demonstration of a large in vivo uptake of radio-labelled progesterone (8) and a progesterone-iqduced increase of R N A synthesis (9) in the cerebellum and cerebral cortex. Furthermore, these constitutively expressed PR in the CNS have recently been implicated in progesterone-mediated behaviours other than sexual behaviour, such as aggressiveness ( 1 9).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(10) have demonstrated that progesterone was able to modify pituitary luteinizing hormone secretion in the rat, even in the absence of circulating oestrogens, through its effects exerted upon the cerebellum and the amygdala. This observation is in line with the demonstration of a large in vivo uptake of radio-labelled progesterone (8) and a progesterone-iqduced increase of R N A synthesis (9) in the cerebellum and cerebral cortex. Furthermore, these constitutively expressed PR in the CNS have recently been implicated in progesterone-mediated behaviours other than sexual behaviour, such as aggressiveness ( 1 9).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the immunoreactive behaviour of the two PR populations was also studied using a purified preparation of immunoglobulins raised against the oestrogen-dependent PR. The finding that progesterone induces neuroendocrine effects which require hormone-genome interaction in brain areas (8)(9)(10) which exclusively contain oestrogen-insensitive PR, provided additional reasons for conducting this study. 800 pg protein) were incubated with 0.4 nM [3H]-R 5020 in the presence or absence of an excess (100 x ) of radioinert R 5020.…”
mentioning
confidence: 99%
“…Nevertheless, numerous studies have reported that cerebellar biochemistry was affected by gonadal hormones (Eleftheriou, Desjardins, & Pattison, 1970;Hudson, Vernadakis, & Timiras, 1970;Litteria & Timiras, 1970;McEwen & Pfaff, 1970;Pfaff, 1968;Seiki & Hattori, 1971;Seiki, Miyamoto, Yamashita, & Kotani, 1969). One possible functional importance of these effects might be in the control of hormone secretions.…”
Section: Evidence Oj Emotional-motivational Involvementmentioning
confidence: 99%